PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN PASIEN POLI UMUM PADA KLINIK SUKAMAJU TAPOS DEPOK - Rosento, Rosento; Susilowati, Isnurrini Hidayat; Saadah, Dedeh (RJABM (Research Journal of Accounting and Business Management), 2021)
ABSTRACT Service is an activity to serve customer needs. Companies engaged in products or services can provide the best service so that they can provide satisfaction to customers. The research objective was to find out how much influence the service had on customer aging at the Primary Outpatient Clinic of Sukamaju Tapos Depok. This research is a quantitative study with data calculation using SPSS version 16. The population taken is the average data of patient visits in a day, namely 79 patients. The sample in this study was 65 samples using the random sampling method. The research instrument used a questionnaire with a total of 30 (thirty) statement items. Based on data analysis, the results of the study on a correlation coefficient of 0.872 indicate that service quality has a strong relationship with customer satisfaction. From the determination coefficient test, it was found that the contribution of service variables to patient satisfaction was 79.4% and the remaining 20.6% was influenced by other variables not examined by the author. The simple regression results obtained 13,878 showed good with unidirectional constants and it can be concluded that the effect of service quality on satisfaction at the Sukamaju clinic has a significant effect. Keywords: Service Quality, Customer Satisfaction.